O efeito de Gesamtkunstwerk em literatura: uma leitura de “O Violino”, de Luiz Vilela, “Miss Brill”, de Katherine Mansfield, e “Aquele Bêbado”, de Carlos Drummond de Andrade - Oliveira, Aline Carrijo de (2021)
The Gesamtkunstwerk concept, elaborated by the German composer Richard Wagner (1813-1883), refers in its essence to the operatic composition. According to that Wagnerian ideology, the opera text allows the confluence between all the artistic elements for bringing: melody by means of the musical instruments; lyrics in the line of the singers; drama originated from the performances; and images provided by the intertwining of the setting and costumes on stage. From this understanding, the present thesis aims to analyse three short stories under the Gesamtkunstwerk concept, and this action is corroborated in the architectural sense of the corpus analysed here, in which the demiurge conceives and prepares a fictional universe to their reader. In the process regarding production, the writer, aware of other qualia, absorbs their essence and mingles them into the literary code/text evoking the reader’s senses, who on their turn apprehend and/or recall a literary effect of Gesamtkunstwerk. In order to reach this objective, one intends to analyse the relation between literature and the other arts, focusing on the interpretation of the short stories “O Violino” (“The Violin”), by Luiz Vilela, “Miss Brill”, by Katherine Mansfield, and “Aquele Bêbado” (“That Drunkard”), by Carlos Drummond de Andrade.